Traceable S-parameter measurements up to 90 GHz in 1.35 mm coaxial. (1st June 2023) - Stokes, Daniel; Gellersen, Frauke; Allal, Djamel; Skinner, James; Phung, Gia Ngoc; Kuhlmann, Karsten
Abstract: As part of a joint program three National Measurement Institutes around Europe—the National Physical Laboratory in the UK, the Physikalisch-Technische Bundesanstalt in Germany and the Laboratoire National de métrologie et d'essais in France—have each established new capabilities for the traceable measurement of S-parameters up to 90 GHz in the new 1.35 mm (E band) coaxial connector. Each institution has established their own measurement systems to access the full frequency band for the connector, utilising a variety of commercially available equipment and measurement setups. Each have also developed their own calibration techniques and verification methods using different vector network analyser calibration routines. These include optimised multi-line Through Reflect Line, multiple Offset Shorts Through and Short Open Load Reciprocal (SOLR) schemes. Uncertainties for each of these setups and calibration schemes were determined utilising theoretical models of the systems and calibration standards, or through verification methods, with different effects being derived from the dimensional characteristics for each of the different standards or verification artifacts. The different dimensional systems used to make these measurements were also developed and established previously as part of the same program. The last part of this exercise was a three-way intercomparison between the laboratories. The comparison involved the measurement of a set of four traveling standards, including both 1-port and 2-port as well as plug (male) and jack (female) devices, each with different reflection and transmission characteristics to better test and demonstrate the equivalence of the capabilities.